CNSC-09. THE NEUROENDOCRINE FACTOR VGF IS NECESSARY FOR THE MAINTENANCE OF THE TUMOR STEM CELL POPULATION IN GLIOBLASTOMA. (14th November 2022) - Kundu, Somanath; Venskus, Abigail; Quiruz, Lee; Longo, John; Longo, Sharon; Walker, Jamie; Richardson, Timothy; Viapiano, Mariano
Abstract: A major factor that contributes to the unchecked growth and recurrence of glioblastoma (GBM) tumors is the presence of a heterogeneous population of GBM stem-like cells (GSCs) that continuously replenish the tumor mass. Targeting strategies against this key cell population have rarely considered the trophic signals from peritumoral neural cells, which can protect the tumor cells during therapy and therefore promote recurrence. Here, we have focused on the little-known secreted factor VGF and its derived neuropeptides, which are largely restricted to the CNS and mediate paracrine communication between neural cells. We analyzed over 200 tissue specimens and cultured GBM cells, demonstrating that VGF is upregulated in malignant gliomas and expressed in GSCs of different subtypes, although it is markedly reduced in differentiated GBM cells. More importantly, we detected VGF expression in peritumoral astrocytes, even though this neuroendocrine factor has never been described in glial cells in normal brain. Co-culture experiments and scRNAseq data from clinical tumors confirmed that VGF is expressed in tumor-associated astrocytes, suggesting that these cells are a paracrine source of VGF in GBM. Accordingly, purified exogenous VGF increased the proliferation of GSCs and rescued GSC viability when the tumor cells were treated with the chemotherapeutic temozolomide. Moreover, purified VGF decreased the expression of inflammatory cytokines in activated macrophages, suggesting that this factor may also contribute to local immunosuppression in gliomas. Conversely, knockdown of VGF in GSCs was sufficient to decrease their viability, self-renewal, and expression of stemness-related genes. At the molecular level, VGF increased intracellular calcium and Akt/mTOR signaling in GSCs, suggesting a possible G protein coupled receptor-mediated mechanism of action. Taken together, our results explore for the first time the role of brain-derived VGF in GBM progression, highlighting the importance of disrupting the communication between the tumor and its microenvironment to achieve long-term anti-tumor efficacy.